2013
DOI: 10.3922/j.psns.2013.3.16
|View full text |Cite
|
Sign up to set email alerts
|

Do people adjust career choices according to socioeconomic conditions? An evolutionary analysis of future discounting.

Abstract: The ability to process environmental cues and make advantageous choices has been fundamental during human evolution. Discounting future rewards is a capacity of our evolved mind and could be useful for understanding career decisions. This paper investigated the relationship between real-life plans, career choices, and income indicators based on an evolutionary approach of future discounting. Study 1 analyzed the plans of 200 senior high school students, and Study 2 analyzed a database of 46,649 applicants to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…In particular, family influence, occupational interest/enjoyment, intellectual stimulation, and living up to potential appear to reflect issues of concern for intellectually gifted adolescents in general, as these adolescents have been noted to prioritize interest over areas of ability (Gottfredson, 2003), desire a sense of satisfaction and accomplishment (Emmett & Minor, 1993), aspire to challenge (Emmett & Minor, 1993;Jung, 2014), and are sensitive to the expectations of their families to fulfil their promise (Emmett & Minor, 1993;Muratori & Smith, 2015). Furthermore, the existence of stability, an expectancy for success, and family influence in the final model appears to be consistent with the importance placed on financial security and financial survival (Gore et al, 2015;Mello, 2009), the consideration of any risks of failure (Leitão et al, 2013), and the sensitivity to the influence of siblings (Ali et al, 2005) by adolescents of low socioeconomic status backgrounds. Nevertheless, of these constructs, only two that have been identified as being salient to the career decisions of intellectually gifted adolescents (i.e., occupational interest/enjoyment and intellectual stimulation) and one that has been identified as being salient to the career decisions of adolescents of low socioeconomic status backgrounds (i.e., an expectancy for success) appear to be directly and positively associated with the construct that predicts occupational intentions for economically disadvantaged intellectually gifted adolescents.…”
Section: Discussionmentioning
confidence: 59%
“…In particular, family influence, occupational interest/enjoyment, intellectual stimulation, and living up to potential appear to reflect issues of concern for intellectually gifted adolescents in general, as these adolescents have been noted to prioritize interest over areas of ability (Gottfredson, 2003), desire a sense of satisfaction and accomplishment (Emmett & Minor, 1993), aspire to challenge (Emmett & Minor, 1993;Jung, 2014), and are sensitive to the expectations of their families to fulfil their promise (Emmett & Minor, 1993;Muratori & Smith, 2015). Furthermore, the existence of stability, an expectancy for success, and family influence in the final model appears to be consistent with the importance placed on financial security and financial survival (Gore et al, 2015;Mello, 2009), the consideration of any risks of failure (Leitão et al, 2013), and the sensitivity to the influence of siblings (Ali et al, 2005) by adolescents of low socioeconomic status backgrounds. Nevertheless, of these constructs, only two that have been identified as being salient to the career decisions of intellectually gifted adolescents (i.e., occupational interest/enjoyment and intellectual stimulation) and one that has been identified as being salient to the career decisions of adolescents of low socioeconomic status backgrounds (i.e., an expectancy for success) appear to be directly and positively associated with the construct that predicts occupational intentions for economically disadvantaged intellectually gifted adolescents.…”
Section: Discussionmentioning
confidence: 59%
“…It is generally accepted that career choices are based on a combination of interests and aptitude of the individuals as well as familial and environmental influences. Several authors provided models to highlight the importance of socioeconomic factors in career planning [ 21 ],however, the impact of such variables on the occupational choices of individuals has not always been well addressed [ 22 ] .We have attempted to highlight this aspect in the current study and found significant differences between students from different backgrounds and socioeconomic conditions.…”
Section: Discussionmentioning
confidence: 86%
“…Shumba and Naong (2013) found that 69.2% of their respondents bemoaned either a lack of or inadequate family income as the most common impediment towards realising their chosen career choice. Meanwhile, a study from Brazil suggests that individuals will adjust career plans and choices according to their socioeconomic conditions (Leitão et al 2013). In many countries including Malaysia, the participation of women in the labour force has greatly increased and many women work outside the home for a substantial part of their lives.…”
Section: Background Characteristicsmentioning
confidence: 99%